2014
DOI: 10.12809/hkmj144246
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of prothrombin complex concentrate in decreasing neurological deterioration in patients with warfarin-associated intracerebral haemorrhage

Abstract: Objective: To compare the outcomes of patients with warfarin-associated intracerebral haemorrhage given different treatments to reverse the effect of anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
2
9
0
1
Order By: Relevance
“…14 Potential reasons for this include differences in study design, early referral to stroke units, the widespread use and avail-PCC for VKA-Associated ICH studies that reported hematoma expansion outcomes generally favored the use of PCC over plasma, 31,33,39 or showed no signficant difference between groups. 32 Overall, there is currently a lack of comparative evidence from RCTs in this population, with only 1 recent RCT conducted in patients with VKA-associated ICH. 39 Although other controlled comparisons of PCC and plasma have been conducted for urgent VKA reversal in cases of major bleeding 44 or prior to urgent surgical procedures, 45 these studies included few patients with ICH.…”
mentioning
confidence: 99%
“…14 Potential reasons for this include differences in study design, early referral to stroke units, the widespread use and avail-PCC for VKA-Associated ICH studies that reported hematoma expansion outcomes generally favored the use of PCC over plasma, 31,33,39 or showed no signficant difference between groups. 32 Overall, there is currently a lack of comparative evidence from RCTs in this population, with only 1 recent RCT conducted in patients with VKA-associated ICH. 39 Although other controlled comparisons of PCC and plasma have been conducted for urgent VKA reversal in cases of major bleeding 44 or prior to urgent surgical procedures, 45 these studies included few patients with ICH.…”
mentioning
confidence: 99%
“…In 2014, Fong et al [9] in a historical cohort study compared patients with intracranial haemorrhage related to warfarin who received either PCC or FFP. After 24 hours, the median INR value changed from 2.8 to 1.2 upon PCC administration.…”
Section: Discussionmentioning
confidence: 99%
“…There were no thrombotic problems [9]. How FFP is not a pure composite, maybe other substances could disturb coagulation properties, becoming it less effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В настоящее время многие клиницисты рассматривают КПК как серьезную альтернативу применению СЗП при коагулопатиях, обусловленных печеночной недостаточностью, и кровотечениях различной этиологии [13][14][15][16].…”
Section: таблица 1 препараты факторов свертывания кровиunclassified